Quantitative study: assessing technological problem solving and thinking skills among primary school children - Anna Felicia; Sabariah Sharif; Wong, WK; Muralindran Mariappan (Penerbit Universiti Kebangsaan Malaysia, 2018)
This program was conducted to analyze the effect of a robotic program in assessing technological problem-solving among primary school children. The content of learning module, which consist of technological problem-solving as well as visible thinking activities, had gone through expert validation before the analytical calculation commenced. Technological Problem Solving Inventory (PSI-TECH) was utilised to measure the technological problem solving. Quasi-experiments were implemented in this study, involving experimental and control group which were equal and homogeneous in selected characteristics. The robotic and basic visual coding program was conducted for five months, with an hour of lesson each week, consistent with the school syllabus and activities. Results were obtained by collecting the data before and after the program following a quantitative analysis of t-test and MANOVA. Result had shown a significance positive value for the experimental group after the program. This study contributes in the field of education, in investigating the technological problem-solving skills among students. In addition, help to diversify the studies in the field of robotics.